Curative external beam radiotherapy in patients over 80 years of age with localized prostate cancer: A retrospective rare cancer network study - (:unkn) unknown (ELSEVIER SCIENCE INC, 2010)
Purpose: To analyse tolerance and outcome of patients over 80 years of age who choose external beam radiation therapy to the prostate as a curative treatment. Methods and material: We evaluated acute and late side effects, biological DFS (bDFS) and actuarial survival as well as causes of death in relation to the clinical status including co-morbidity, PSA value, Gleason score and modalities of external radiotherapy in patients with localised prostate cancer >80 years of age. Results: From January 1990 to December 2000, 65 eligible cases (median age: 81) were treated by 12 different participating institutions in the Rare Cancer Network. Tumour stage was TIN0M0, T2N0M0 and T3N0M0 for 10, 40, and 15 patients, respectively. Median follow-up was 65 months (range 22-177). Five-year overall survival rate was 77% with a 5-year bDFS rate of 73%. The incidence of grade 3 early toxicity was 12% and 9% for urinary and digestive tract, respectively. Conclusions: Radiation therapy given with curative intent is well tolerated in this selected group of patients aged over 80 years with localised prostate cancer. Results in terms of survival do not suggest a deleterious impact of this treatment. Therefore the authors recommend that radiation therapy with curative intent should not he withheld in selected elderly patients with localised prostate cancer. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Prostate cancer; Elderly; Radiotherapy; Side effects; Curative treatment; RADIATION-THERAPY; ELDERLY-PATIENTS; OLDER MEN; COMORBIDITY; DEATH; MANAGEMENT; CARCINOMA; SURVIVAL; TOXICITY; OUTCOMES